2021
DOI: 10.31234/osf.io/8y57u
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early visual deprivation does not prevent the emergence of basic numerical abilities in blind children.

Abstract: Studies involving congenitally blind adults demonstrated that visual experience is not a mandatory prerequisite for the emergence of efficient numerical abilities. It remains however unknown whether blind adults developed lifelong strategies to compensate for the absence of foundations vision would provide in infancy. We therefore assessed basic numerical abilities in blind and sighted children of 6 to 13 years old. We also assessed verbal and spatial working memory abilities and their relationship with mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…They generally include children or adults with vision loss, due to congenital disorders of the peripheral visual system, in the absence of any other cognitive deficit. Their performance was found equalif not superiorto the performance of sighted people in numerical judgments (Castronovo & Seron, 2007), counting (Crollen et al, 2014), estimation (Castronovo & Delvenne, 2013;Ferrand et al, 2010), working memory (Crollen et al, 2021) or arithmetic (Dormal et al, 2016). In the same time, finger counting was less often observed among blind than sighted children and when they were explicitly asked to rely on finger counting, blind children preferred tapping on the table or touching their fingertips with the other hand.…”
Section: The Need For Decisive Evidencementioning
confidence: 86%
See 1 more Smart Citation
“…They generally include children or adults with vision loss, due to congenital disorders of the peripheral visual system, in the absence of any other cognitive deficit. Their performance was found equalif not superiorto the performance of sighted people in numerical judgments (Castronovo & Seron, 2007), counting (Crollen et al, 2014), estimation (Castronovo & Delvenne, 2013;Ferrand et al, 2010), working memory (Crollen et al, 2021) or arithmetic (Dormal et al, 2016). In the same time, finger counting was less often observed among blind than sighted children and when they were explicitly asked to rely on finger counting, blind children preferred tapping on the table or touching their fingertips with the other hand.…”
Section: The Need For Decisive Evidencementioning
confidence: 86%
“…Under an embodied view, it is reasonable to assume a progression from overt to covert counting so that children get able to support enumeration through very subtle movements that cannot be easily detected with standard behavioural methods (Wilson, 2002). A longitudinal study from kindergarten might actually reveal that blind children shift more rapidly than sighted to covert counting because of superior working memory capacity (Crollen et al, 2021).…”
Section: The Need For Decisive Evidencementioning
confidence: 99%
“…Responses were recorded by the experimenter standing behind the participants' seats and seeing the graduations of the graph paper. As in Crollen et al 38 , performance at the task was measured as Percentage of Absolute Error (i.e., PAE), which corresponds to the absolute value of the Percentage of Error (i.e., PE). The PE for each number was computed: ((participant's number estimation − true number)/line's scale) * 100.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, most of existing studies investigated numerical performance in visually impaired adults rather than children. To our knowledge, only one study 38 assessed the performance of congenitally blind children in a series of visuospatial numerical tasks (number-to-position, number bisection, counting, and mathematical operations). The authors reported that visual deprivation from birth does not affect numerical performance, which seems to affect the association between arithmetic competence and working memory mechanisms.…”
mentioning
confidence: 99%
See 1 more Smart Citation